P370 Maintenance of health-related quality of life improvements with upadacitinib treatment among patients with moderately to severely active ulcerative colitis: results from, 52-week phase, 3 study U ACHIEVE maintenance. (21st January 2022) - Panés, J; Loftus, E V J; Higgins, P; Lindsay, J O; Zhou, W; Yao, X; Ilo, D; Phillips, C; Tran, J; Sanchez Gonzalez, Y; Vermeire, S
Abstract: Background: Health-related quality of life (HRQOL) is reduced in patients (pts) with ulcerative colitis (UC). We report on the HRQOL benefits of maintenance treatment with upadacitinib (UPA), a selective and reversible Janus kinase inhibitor, in pts with moderately to severely active UC in the Phase, 3 multicentre, randomised, double-blind U-ACHIEVE maintenance study (NCT02819635). Methods: This study included a primary analysis of, 451 pts who achieved clinical response following treatment with UPA, 45 mg once daily (QD) in two replicate, 8-week induction studies, U-ACHIEVE induction, and U-ACCOMPLISH (NCT03653026). In U-ACHIEVE maintenance, pts from both induction studies were re-randomised, 1:1:1 to receive QD UPA, 15 mg, UPA, 30 mg, or PBO. HRQOL outcomes evaluated included the percent of pts reporting a clinically meaningful within-person change (MWPC) from induction baseline to Week, 0 (maintenance baseline) and Week, 52 (end of maintenance) in a broad range of HRQOL measures, including Inflammatory Bowel Disease Questionnaire (IBDQ), Work Productivity and Impairment Questionnaire (WPAI), Short Form, 36 (SF-36), European Quality of Life-5 Dimensions, 5 Levels (EQ-5D-5L), and Ulcerative Colitis Symptoms Questionnaire (UC-SQ). Results: A total of, 149, 148, and, 154 pts received PBO, UPA, 15 mg, and UPA, 30 mg QD, respectively, during maintenance. At Week, 0 of the maintenance study, there were no significant differences between UPA and PBO treatment groups in the percentage of pts reporting MWPC relative to induction baseline for most pt-reported outcomes (PROs) as all pts enrolled in maintenance were UPA clinical responders during IP. For IBDQ, a significantly greater proportion of pts achieved MWPC criteria ( p <0.001) with UPA, 15 mg (68.9%) and UPA, 30 mg (78.6%) vs, 39.6% for PBO at Week, 52 (Figure, 1 ). Also, a significantly greater proportion of pts treated with either, 15 mg or, 30 mg UPA dosage vs PBO over, 52 weeks achieved MWPC for the WPAI domains ( p ≤0.01) of overall work improvement, presenteeism, and activity impairment (Figure, 2 ), in both physical and mental component summaries of SF-36 ( p <0.001, Figure, 3 ), in EQ-5D-5L ( p <0.001, Figure, 4 ), and in UC-SQ ( p <0.001). A numerically greater proportion of pts receiving UPA, 30 mg vs, 15 mg achieved MWPC in most PROs at Week 52. Conclusion: A significantly higher percentage of pts with moderately to severely active UC who responded to UPA induction therapy maintained clinically meaningful improvements with UPA, 15 mg of, 30 mg compared to PBO consistently across a broad range of HRQOL outcomes after, 52 weeks of maintenance treatment. These HRQOL aspects include IBD symptoms (IBDQ, UC-SQ), work productivity (WPAI), physical and mental functioning (SF-36), and general well-being (IBDQ, EQ-5D).